Adapting the competences of the employed personnel in the context of the integration of artificial intelligence in organizations - Ioana Maria Popescu; Iuliana Zavatin; Daniela-Ioana Manea; Rodica Pamfilie; Alexandru Jurconi (Amfiteatru Economic, 2024)
Artificial intelligence (AI) has been part of organisational activity for a long time, but until the launch of the ChatGPT application at the end of 2022, it was not discussed in such a comprehensive way. This type of application brought to the public's attention the concept of artificial intelligence and the fact that some of the repetitive activities of employees could easily be taken over by such applications. The article aims to identify trends in the evolution of skills among employees in the context of the integration of AI into the activity of organisations, based on empirical exploratory research, carried out between January and February 2024, on a sample of 259 respondents. The data were obtained by applying an online questionnaire on a specialised platform, the questionnaire having 21 questions, of which the first eight outline the sociodemographic profile of the respondents. The originality of the article consists of conducting empirical research with the aim of matching the sociodemographic characteristics of the respondents with their approach toward the acquisition of skills in the context of the inclusion of AI in the activities of the organisation in which they operate. To validate the research hypotheses, non-parametric analysis methods of the interdependencies between the variables were used, the results obtained highlighting the need to study this issue on a representative sample, using a more complex questionnaire. More than 75% of respondents to the study are interested in acquiring skills to use AI-based applications. The most significant risks identified, as a result of the integration of AI in organisations, are the alteration of interpersonal communication and staff restructuring, and the greatest opportunity is the decrease in the time allocated for the performance of certain tasks, reflected in the increase in the efficiency of the organisation. The relevance of the research derives from the need to deepen several aspects related to the evolution of employee skills, in the context of increasing concern related to the way in which AI is being adopted by organisations.
Keywords: J24; O15; O33; C25; 330; artificial intelligence (AI); attitude toward artificial intelligence; Chat Generative Pre-trained Transformer (ChatGPT); employee professional skills; non-parametric analysis; the Organisation for Economic Cooperation and Development (OECD)